Depending on session-typed processes - Toninho, Bernardo (2019)
The authors would like to thank the anonymous reviews for their comments and suggestions. This work is partially supported by EPSRC EP/K034413/1, EP/K011715/1, EP/L00058X/1, EP/N027833/1, EP/N028201/1 and NOVA LINCS (UID/CEC/04516/2013).